ALSUntangled 59: Tamoxifen: The Alsuntangled Group. Issue 7 (2nd October 2021) - Bedlack, Richard; Kihuwa-mani, Sky; Barkhaus, Paul E.; Bereman, Michael; Caress, James B.; Crayle, Jesse; Pattee, Gary L.; Heiman Patterson, Terry; Wicks, Paul; Zach, Neta; Carter, Gregory T.; Salmon, Kristiana
Abstract: Here we use the ALSUntangled methodology to review Tamoxifen as an ALS treatment. We show that it has plausible mechanisms, a positive preclinical study, a case report and 2 small trials suggesting benefits. We show that it appears reasonably safe, though there is a small risk of developing cancer with long term use. While we cannot yet endorse this as an ALS treatment, there is enough evidence to warrant another larger ALS trial.